SUSTAINED MONITORING OF THE SOUTHERN OCEAN AT DRAKE PASSAGE: PAST ACHIEVEMENTS AND FUTURE PRIORITIES - Meredith, M; Woodworth, P; Chereskin, T; Marshall, D; Allison, L; Bigg, G; Donohue, K; Heywood, K; Hughes, C; Hibbert, A; Hogg, A; Johnson, H; et al. (2011)
Drake Passage is the narrowest constriction of the Antarctic Circumpolar Current (ACC) in the Southern Ocean, with implications for global ocean circulation and climate. We review the long-term sustained monitoring programs that have been conducted at Drake Passage, dating back to the early part of the twentieth century. Attention is drawn to numerous breakthroughs that have been made from these programs, including (1) the first determinations of the complex ACC structure and early quantifications of its transport; (2) realization that the ACC transport is remarkably steady over interannual and longer periods, and a growing understanding of the processes responsible for this; (3) recognition of the role of coupled climate modes in dictating the horizontal transport and the role of anthropogenic processes in this; and (4) understanding of mechanisms driving changes in both the upper and lower limbs of the Southern Ocean overturning circulation and their impacts. It is argued that monitoring of this passage remains a high priority for oceanographic and climate research but that strategic improvements could be made concerning how this is conducted. In particular, long-term programs should concentrate on delivering quantifications of key variables of direct relevance to large-scale environmental issues: In this context, the time-varying overturning circulation is, if anything, even more compelling a target than the ACC flow. Further, there is a need for better international resource sharing and improved spatiotemporal coordination of the measurements. If achieved, the improvements in understanding of important climatic issues deriving from Drake Passage monitoring can be sustained into the future. © 2011 by the American Geophysical Union.